Critical Discourse Analysis on Linguistic Ideology of The Netizens Comments (ADI Journal on Recent Innovation (AJRI), 2022)
This study aims to analyze linguistics ideology. The data were collected from the netizens' comment columns on KompasTv YouTube Channel. They were about the response to the Minister of Religious Affairs' speech entitled Minister of Religion Yaqut Cholil's Words About the Regulation of Mosque Loudspeakers Maximum 100 Decibels. The researchers applied a descriptive qualitative approach. Which has the purpose of finding out the two dimensions of Van Dijk's theory, namely Macrostructure and Microstructure. The result of a research analysis was that in Macrostructure, there were Disagreement, Agreement, Advice, Tolerance from Non-Muslims, and Bad Wishes, whereas, in Microstructure, it was found Schematic, Syntactic, and Rhetoric